The reliability and validity of the social responsiveness scale to measure autism symptomology in Vietnamese children - Nguyen, Phuong Hong; Ocansey, Maku E.; Miller, Meghan; Le, Dung T. K.; Schmidt, Rebecca J.; Prado, Elizabeth L. (John Wiley & Sons, 2019)
The Social Responsiveness Scale (SRS) has been validated in high‐income countries but not yet in low‐ and middle‐income countries. We aimed to assess the reliability of the SRS in a community sample and its validity to discriminate between children with and without autism spectrum disorder (ASD) in Vietnam. We used a three‐phase study: piloting the translated SRS, reliability testing, and validation of the SRS in 158 Vietnamese caretakers and their children (ages 4–9 years). We examined reliability, validity and sensitivity, and specificity to ASD diagnosis. We applied receiver operator characteristic (ROC) analysis to determine optimal cutoff scores discriminating the children with ASD from those without ASD. We also assessed the performance of the SRS short form. We found that reliability was good with high internal consistency (0.88–0.89), test–retest reliability (0.82–0.83), sensitivity (93%), and specificity (98%) for identification of children with ASD. The ROC curves were similar for total raw score and total T‐score, with the area under the curve (AUC) values reaching 0.98 and the optimal cutoff of 62 for raw scores and 60 for T‐scores. The SRS short form also performed well in distinguishing children with ASD from children without ASD, with high AUC (0.98), sensitivity (90%), and specificity (98%) when using a raw score of 15 as a cutoff. In conclusion, the translated and culturally adapted SRS shows good reliability, validity, and sensitivity for identification of children with ASD in Vietnam. Both SRS long and short forms performed adequately to discriminate between children with and without ASD. Autism Res 2019, 00: 1–13. © 2019 International Society for Autism Research, Wiley Periodicals, Inc.Middle‐income countries often lack validated tools to evaluate autism symptoms. The Social Responsiveness Scale (SRS) translated to Vietnamese was reliable and performed well to distinguish between children with and without autism spectrum disorder in Vietnam. The Vietnamese SRS, and translations of the tool to other languages with this methodology, may be useful in pediatric practice, potentially allowing providers to make more appropriate referrals for diagnostic evaluations and identify children for intervention to help them fulfill their developmental potential.